Math, asked by Palak1134, 1 year ago

8a3+b3+1-6ab Factorize

Answers

Answered by xyz99
22
8a3+ b3 +1 - 6ab
=(2a)3 +b3 + 1×1×1 - 3 ×2a × b×1
=(2a+b+1){(2b)2+(b)2+1×1-2a×b-b×1 - 1×2a}
=(2a+b+1)(4b2+ b2 + 1 -2ab-b-2a)
Answered by anchitpatel777
25

Answer:

8a³ + b³ + 1 - 6ab

= (2a)³ + (b)³ + 1³ - 3(2a)(b)(1)

= [2a + b + 1][(2a)²+ b² + 1² - (2a)b - (2a)1 - b(1)]

=   [2a + b + 1][(4a²+ b² + 1 - 2ab - 2a - b]

identity used

= x³ + y³ + z³– 3xyz = (x + y + z) (x² + y² + z² – xy – yz – zx)

Similar questions